The pattern of bacterias causes pneumonia on Sardjito General Hospital January 1, 1990 - December 31, 1994 - Barmawi Hisyam Barmawi Hisyam (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Pneumonia has high morbidity and mortality. The clinical classification of Community Acquired Pneumonia (CAP) and Hospital Acquired Pneumonia (HAP) and the empirical treatment have beneficial means to prevent the severity of the disease. A retrospective study had been conducted, by evaluating the medical record of the patients hospitalised in the Department of Internal Medicine Dr. Sardjito General Hospital, January 1, 1990 -December 31, 1994. There were 221 cases of pneumonia, the major frequency on range 45-64 years old: 84 (38,01%), men/women ratio: 1.5 : 1. The CAP was more than HAP: 200 (90,50%) vs 21 (9,50%). Bacterias causes CAP: Streptococcus alpha 36 (29,75%), Staphylococcus aureus 28 (23,14%) and Klebsiella pneumonia 27 (22,31%). While the bacteria cause of typical HAP: Klebsiella pneumoniae 1 (100%), mixed bacterias causes HAP: Streptococcus alpha 3 (33,33%), Staphylococcus aureus 3 (33,33%) and Klebsiella pneumoniae 2 (22,22%). There were no difference the pattern of bacterias causes CAP or HAP.Key Words : the pattern of bacteria - typical bacteria - mixed bacterias - CAP - HAP